Effect of urbanism, course, year level and religiosity on tolerance - Agdeppa, Joyce G.; De Dios, Ederlyne C. (1994)
This study was conducted on the premise that tolerance is a necessary factor in maintaining a stable society. It was aimed at finding the possible target of intolerance among UPCB students and the relationship between tolerance and some of the factors hypothesized to affect it, namely: urbanism, year level, course and religiosity. The study made use of a one-shot survey for research design and was conducted inside the University of the Philippines College Baguio Campus with the undergraduate students as respondents. Cross-tabulations were made between the variables and the relationship were identified by computing for Tau C and Chi-square. The result of the study showed that : (a) gays, lesbians, and born-again Christians are the usual target of intolerance among UPCB students and that (b) there is minimal support to the relationship between tolerance and some of the factors associated with it. Out of the fourteen questions on tolerance, only four are related to urbanism, five are related to year level, none is related to course, and only one is related to religiosity. The study also found out that most UPCB students are willing to tolerate actions or activities (by members of their least-liked group) which maybe considered harmless like using public utilities, and writing a book ; they are moderately tolerant in aspects where they will be personally forced to communicate with such individuals (like being friends with them and trusting them) ; and they are definitely intolerant in aspects where they will have to spend most, if not the rest of their lives, with the said deviant individuals -- Author's abstract.